Mechanika biurokracji w serialu „The Wire” - Machaj, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to illustrate policy considerations on bureaus, presented in the TV series The Wire. We plan to show that significant theoretical contributions to the economics of bureaucracy have been well presented by the creators of the show. It could even be stated that this series is the first TV treatise about social institutions, bureaus in particular. The first section describes inherent causes limiting implementations of political plans. The second section focuses on the series’ most significant contribution, that is portraying the hyperparametrization of bureaus. The third section relates methodological individualism to the context of bureaucratic determinism.
Keywords: biurokracja; The Wire; instytucje polityka; szkoła wyboru publicznego